Characterization of the complete chloroplast genome of Cucun mismelo L. var. Agrestis Naud. Issue 3 (2nd July 2020) - Hui, Linchong; Xu, Weiping; Chen, Wei; Zhou, Zhenling; Li, Jingfang; Ma, Teng; Feng, Shida; Xu, Yan; Zhao, Tongli; Yang, Haifeng
Abstract: Cucumis melo L. var. Agrestis Naud chloroplast genome sequence was first reported. The size of the chloroplast genome is 156, 016 bp in length, including a large single copy region (LSC) of 86, 334 bp, a small single copy region (SSC) of 18, 088 bp, and a pair of inverted repeat (IRa and IRb) regions with 25, 797 bp. Cucumis melo L. var. Agrestis Naud chloroplast genome encodes 133 genes, including 88 mRNA genes, 37 tRNA genes, and eight rRNA genes. Phylogenetic analysis with the reported chloroplast sequences shows that Cucumis melo L. var. Agrestis Naud was closely related to Cucumis melo subsp. melo.